Thorndike's Credo: Metaphysics in psychometrics. (June 2020) - Michell, Joel
Endorsing a priori the conviction that any science worthy of the name must measure the attributes it investigates, psychometricians adopted a metaphysical paradigm (without acknowledging it as such) to secure its claim that mental tests measure psychological attributes, a claim that was threatened by the inadequacy of test data to secure it. The fundamental axiom of this paradigm was Thorndike's Credo ("All that exists, exists in some amount and can be measured"; 1918, p. 16), which entails its central lemma, the psychometrician's fallacy ("All ordered attributes are quantitative"; Michell, 2009, p. 41), and which, in turn, supplies psychometrics' primary methodological principle ("interval scales can be derived from ordinal data"). Logically, this framework is flawed at every level: Thorndike's Credo is metaphysical overreach; the psychometrician's fallacy is just that—a logical fallacy; and their primary methodological principle, a prioristic thinking.